1996
DOI: 10.1152/jappl.1996.80.1.245
|View full text |Cite
|
Sign up to set email alerts
|

Influences of gender on sympathetic nerve responses to static exercise

Abstract: We compared reflex responses to static handgrip at 30% maximal voluntary contraction (MVC) in 26 untrained men (mean age 35 +/- 3 yr) and 23 untrained women (mean age 39 +/- 4 yr). Women demonstrated attenuated increases in blood pressure and muscle sympathetic nerve activity (MSNA; by microneurography) compared with men. This difference was also observed during a period of posthandgrip circulatory arrest. 31P-nuclear magnetic resonance (NMR) spectroscopy studies demonstrated attenuations in the production of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
179
2
9

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 175 publications
(202 citation statements)
references
References 0 publications
12
179
2
9
Order By: Relevance
“…Our finding that administration of 17␤-estradiol had no effect on the pressor response to static contraction might appear at first glance to conflict with the finding by Ettinger et al (11), who reported that premenopausal women displayed smaller pressor and muscle sympathetic nerve activity responses to static handgrip than did men of similar age. Ettinger et al attributed this difference to an attenuated muscle metaboreflex in women.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Our finding that administration of 17␤-estradiol had no effect on the pressor response to static contraction might appear at first glance to conflict with the finding by Ettinger et al (11), who reported that premenopausal women displayed smaller pressor and muscle sympathetic nerve activity responses to static handgrip than did men of similar age. Ettinger et al attributed this difference to an attenuated muscle metaboreflex in women.…”
Section: Discussioncontrasting
confidence: 99%
“…Second, and possibly most important, we used cats, whereas Ettinger et al used humans. The importance of this difference, in addition to the obvious difference pertaining to species, is that in cats the metabolic by-products of triceps surae contraction have been measured by microdialysis (23), whereas in humans the by-products for static handgrip have been measured by NMR (11). The time course and the specific metabolites measured by the two techniques were different.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations